« Das Private ist politisch » : journaux d’écrivaines est-allemandes - Anne Kerebel (Itinéraires)
At times of political drift and totalitarian temptation, diaries enable criticism through entrenchment and detachment. Women writers Christa Wolf (1929-2011), Brigitte Reimann (1933-1973) and Maxie Wander (1933-1977) all kept a diary in the GDR, in a “society under supervision” which controlled and censored means of communication and expression, whether private or public. Although none of the authors clearly opposed the regime, they asserted their rights to intimacy and freedom of expression in their diaries. After repositioning the diaries within the context of their writing and publishing, the texts will be confronted in an analysis of the links forged between intimate and political spheres.